Experimental investigation on characteristics of strength recovery and pore structure of Jilin ball clay under freeze–thaw cycles - Gao, Yucong; Hao, Dongxue; Liu, Xuejun; Chen, Kai; Chen, Rong; Guo, Ruifeng (Scientific reports, 2024)
Freeze–thaw cycles are frequently overlooked as a pivotal factor contributing to leakage and structural failures in clayey soil-impermeable barriers used in landfills or tailings repositories in regions subject to seasonal freezing. This investigation explores the recovery and residual strength properties of Jilin ball clay undergoing six freeze–thaw cycles, and assesses the pore structure characteristics through a series of nuclear magnetic resonance (NMR) tests. The results indicate that normal stress has a greater impact on peak recovery strength than dry density and rest periods. Cohesion increases earlier and more significantly during rest periods compared to internal friction angle. Although the pore diameter remains consistent within the micropores during the freeze–thaw cycles, the soil’s structural integrity undergoes notable changes. The concluding analysis provides valuable insights for the construction and management of impermeable barriers in landfills or tailings repositories within seasonally frozen areas.